Analysis of the formation of heat islands from the perspective of different paving materials - Machado Pirani, Leonardo; Lizama, Maria de los Angeles Perez; Zavaski, Felipe; Herek Rezende , Luciana Cristina Soto (Electronic Journal "Fórum Ambiental da Alta Paulista", 2023)
One of the main causes of the phenomenon of heat islands is the high thermal absorption of surface materials and their heat-holding capacity. In order to contribute to the study of materials that help in minimizing the heat generated, the objective was to perform an analysis of temperature and its relationship in the formation of heat islands between four paving materials used in the city of Maringá: asphalt blanket, interlocked cementitious pavement, draining floor, and rubberized waste floor. The densification and urban morphology have influences on the study of the physical behavior of the materials, so four locations were chosen in full sun and shade, in different areas of land use and occupation. The evaluation was carried out using data from the Maringá Meteorological Station, temperature data collected in the field, in the winter period, using mobile transect equipment. The data collected indicate that the asphalt blanket aggregates a greater amount of heat, in contrast to permeable materials, dissipates less heat to the atmosphere, especially after the rains. In the following days the rainfall of the impermeable materials, increases the surface temperature and the relative temperature of the air exponentially, as soon as all the water drains, already the permeable materials, due to the presence of water, increase the surface temperature and relative temperature gradually as the days without rains are prolonged, showing that the permeability of the soil and the amount of vegetation cover are crucial factors for the mitigation of concentrated heat in the centers Urban.